1997
DOI: 10.5144/0256-4947.1997.293
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Deficiency in Saudi Arabia

Abstract: Data on the status of iodine deficiency in the Arabian peninsula is scarce. We have conducted a cross-sectional national epidemiological survey in Saudi Arabia to study the iodine status of Saudi schoolchildren, between eight and ten years, who were randomly selected, after taking into consideration the gender, provincial population and area distribution. Casual urine samples were collected and sent to the central laboratory for analysis. Clinical assessment for the presence of goiter was conducted in four are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 4 publications
1
24
2
1
Order By: Relevance
“…[14] In a study in Saudi Arabia by Al Nuaim et al ., the prevalence of goiter in the studied areas ranged from 8% to 30%. [15] An overall prevalence of 16.8% was estimated in a survey in Yemen by Zein et al . [16]…”
Section: Discussionmentioning
confidence: 99%
“…[14] In a study in Saudi Arabia by Al Nuaim et al ., the prevalence of goiter in the studied areas ranged from 8% to 30%. [15] An overall prevalence of 16.8% was estimated in a survey in Yemen by Zein et al . [16]…”
Section: Discussionmentioning
confidence: 99%
“…A previous cross-sectional study reported a mild degree of iodine deficiency in Saudi school children [15], and the authors recommended that iodized salt be more widely used. However, their findings were in contrast to a report from neighboring Gulf countries, where iodine intake (ug/day) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, iodine deficiency has been a public health problem in the Eastern Mediterranean Region (EMR) countries, particularly in Afghanistan, Algeria, Iraq, Iran, Morocco, Saudi Arabia, Sudan, Yemen, and Pakistan 9, 10, 11, 12, 13, 14, 15, 16. Iran took the first initiative in the region in 1989 and established the Iranian National Committee for control of IDD.…”
Section: Introductionmentioning
confidence: 99%